2017
DOI: 10.1016/j.pmedr.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Community partnerships in healthy eating and lifestyle promotion: A network analysis

Abstract: Promoting healthy eating and lifestyles among populations with limited resources is a complex undertaking that often requires strong partnerships between various agencies. In local communities, these agencies are typically located in different areas, serve diverse subgroups, and operate distinct programs, limiting their communication and interactions with each other. This study assessed the network of agencies in local communities that promote healthy eating and lifestyles among populations with limited resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…In 13 studies, networks were compared (e.g.,, partner strength) by geographic location (rural vs urban), funding, and population served. 106-116 Findings demonstrated that partnership strength including collaboration was lower in rural locations and low-resource settings or for those targeting different ethnic populations. Partnership strength was higher in networks with funding for partnership development.…”
Section: Resultsmentioning
confidence: 99%
“…In 13 studies, networks were compared (e.g.,, partner strength) by geographic location (rural vs urban), funding, and population served. 106-116 Findings demonstrated that partnership strength including collaboration was lower in rural locations and low-resource settings or for those targeting different ethnic populations. Partnership strength was higher in networks with funding for partnership development.…”
Section: Resultsmentioning
confidence: 99%
“…This review also revealed that homophily (i.e., the tendency of organizations to collaborate with other organizations in the same field) seems to be a widespread mechanism among PA promoting networks [ 59 , 60 , 64 , 72 ]. In the field of PA promotion, it seems natural that organizations of the same type are more strongly connected because of the similar nature of work and the comparable organizational settings [ 29 , 73 ]. Cooperation with actors belonging to the same type could also be observed in networks of healthy lifestyle promotion [ 17 , 69 , 74 ]; this circumstance could be avoided, for example, by stringent leadership and coalition-promoting behavior, e.g., by state governments [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resource and cost sharing based on partnerships can also play an important role in intervention sustainability. However, two recent studies assessed the network of agencies in local communities that promote healthy eating among populations with limited resources and found that those agencies were only loosely connected (46,47) . The current review serves as the first attempt to synthesize scientific evidence regarding food pantry-based interventions on participants' diet-related outcomes in the USA.…”
Section: Seligmanmentioning
confidence: 99%